Memorandum of Understanding between the BRAC University, Mohakhali, Dhaka and Bangladesh Atomic Energy Commission, Agargaon, Dhaka (2011) - BRAC University; Bangladesh Atomic Energy Commission (BRAC University and Bangladesh Atomic Energy Commission, 2013)
1. Parties - (a) BRAC University and (b) Bangladesh Atomic Energy Commission (BAEC). 2. Background. 3. Roles of responsibilities of BAEC and BRACU.